The Dynamics of Intercultural Communication between Migrant Students and the Local Community in the City of Padang - Isnaini, Isnaini; Silva, Amanda Purnama; Cania, Carly; Hapina, Dufya; Kurniawan, Faisal; Dani, Ferdi Ahmad; Patriana, Nadira Salsabila (Universitas PGRI Sumatera Barat, 2024)
This study explores the dynamics of intercultural communication between migrant students and the local community in Padang, West Sumatra. The growing presence of students from various regions has led to increasingly complex cultural interactions. Employing a qualitative method with a case study approach, data were collected through interviews, observations, and documentation involving both migrant students and local community members. The findings reveal that intercultural interactions are dynamic but marked by several key challenges, including language barriers, social stereotypes, and differences in cultural values. These challenges can hinder the process of adaptation and social integration for students in their new environment. Nevertheless, adaptation occurs through various strategies such as learning the local language, participating in community activities, and building interpersonal relationships through informal approaches. This study emphasizes the importance of intercultural communication competence as a crucial factor in fostering harmonious social integration within multicultural settings. The ability to understand cultural differences and engage in empathetic communication plays a vital role in minimizing misunderstandings and creating inclusive spaces for interaction. These insights are relevant not only for educational and social policy development but also contribute to the broader discourse on intercultural communication within the diverse sociocultural context of Indonesia